Islamically modified cognitive behavioral therapy: Enhancing outcomes by increasing the cultural congruence of cognitive behavioral therapy self-statements. (May 2016) - Husain, Altaf; Hodge, David R
Cognitive behavioral therapy (CBT) is one of the most widely used and effective therapeutic modalities. When utilized with devout Muslims, however, outcomes may be enhanced by modifying traditional CBT self-statements to reflect Islamic values. Toward this end, the values that inform the Western counseling project are discussed. Areas of differing value emphasis are noted between Islam and traditional CBT. The process of constructing Islamically modified statements is illustrated, and it is proposed that this culturally congruent modality may engender (1) faster recovery, (2) better treatment compliance, (3) lower rates of relapse, and (4) reduced treatment disparities. The article concludes by providing suggestions to assist social workers implement Islamically modified CBT statements in a manner that maximizes the potential to achieve these salutary outcomes.